Iron-based metal organic framework (at) MoS2 / CdS double-Z-type heterojunction nanoreactor as well as preparation method and application thereof
By introducing MoS2 and CdS into the iron-based metal organic framework, a dual Z-type heterojunction nanoreactor was constructed, which solved the problems of low light absorption capacity and poor stability of existing photocatalysts, achieved efficient photocatalytic performance and stability, and significantly improved the removal rate of organic pollutants.
Patent Information
- Application Number
- CN202411650868.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
AI Technical Summary
In actual applications, existing heterophase photocatalysts have problems such as low light absorption capacity, high photogenerated electron hole recombination rate and poor catalyst stability, which limits the application effect of photocatalytic technology.
By introducing MoS2 and CdS into the iron-based metal organic frame (MOF), a double Z-type heterojunction nanoreactor was constructed, and the composite material was prepared by hydrothermal method and in-situ deposition method to construct a photofenton system to improve photocatalytic performance.
Efficient production of H2O2 under visible light was achieved, significantly improving the removal rate of organic pollutants to 98.4% and 99.5%, and the composite material maintained good stability and catalytic activity in multiple cycles.
Smart Images

Figure CN119500281A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of multiphase photocatalysts, and specifically relates to an iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor and a preparation method and application thereof. Background Art
[0002] With the rapid development of industry, industrial production releases a large amount of pollutants into the environment, such as organic pollutants such as dyes and antibiotics, which makes ecological and environmental problems worse and directly or indirectly threatens human health. In order to solve the challenges brought by pollutants in wastewater, various advanced oxidation treatment technologies (AOPs) have been proposed, including ozonation, persulfate oxidation, supercritical oxidation, ultraviolet irradiation and photocatalysis. Advanced oxidation technology has the advantages of high efficiency and wide application range, and can produce active free radicals and quickly transform various pollutants. Among them, photocatalysis technology, as a cost-effective, low-carbon and green emerging technology, has aroused great interest among researchers. Photocatalysis technology can effectively mineralize pollutants into harmless substances (such as CO2, H2O and easily degradable small molecules) by converting light energy into chemical energy. It is environmentally friendly and has good application prospects.
[0003] In recent decades, different types of semiconductor photocatalysts have been used for photocatalytic degradation of pollutants, such as TiO2, g-C3N4, metal organic frameworks (MOFs), etc. MOF is a highly ordered porous crystalline material formed by the coordination of organic ligands with metal ions or clusters. It has the characteristics of large specific surface area and adjustable structure, and has received extensive attention in the field of photocatalysis. However, it still has problems such as wide band gap and low light utilization, which need further improvement.
[0004] Tripathy et al. synthesized a double-linker Zr-MOF containing BDC and BDC-NH2 by a one-step solvothermal method. The introduction of the double linker significantly narrowed the band gap, thereby improving the light absorption capacity. Modification of MOF ligands by introducing functional groups with electron-donating ability can effectively expand the light absorption range, and the introduction of -NH2 is the most commonly used method. In addition, the introduction of metal elements to MOF is also one of the effective ways to narrow the band structure and improve the light harvesting ability. Melillo et al. reported a series of five modified UiO-66MOFs with different metals: Zr, Zr / Ti, Zr / Ce, Zr / Ce / Ti and Ce. Among them, the trimetallic (Zr / Ce / Ti) modified UiO-66 has the highest photocatalytic activity and still retains its activity after repeated use, demonstrating its stability and potential for practical application.
[0005] The Fenton reaction is a classic advanced oxidation process. In the Fenton reaction, ferrous ions and hydrogen peroxide react under acidic conditions to produce strong oxidizing free radicals, such as OH, which can effectively remove refractory organic pollutants. However, the Fenton reaction is only stable under acidic conditions, and the pH value needs to be adjusted continuously during the reaction. 2+ The regeneration of the photocatalytic reaction leads to a decrease in the degradation efficiency, thus limiting the application of the Fenton technology. In recent years, people have combined photocatalytic technology with the Fenton reaction to improve the efficiency of pollutant removal through synergistic effects. Ultraviolet light or visible light is introduced into the Fenton reaction through semiconductor light absorption, which promotes the generation rate of free radicals and accelerates the Fe 2+ / Fe 3+ circulation, thereby improving the utilization rate of hydrogen peroxide.
[0006] Wang et al. prepared NH2-MIL-88B with ligand defects by doping with monodentate ligands, which significantly improved the photo-Fenton catalytic degradation performance. Therefore, by constructing a photo-Fenton system, hydrogen peroxide can be spontaneously generated on the catalyst interface without the need for additional hydrogen peroxide addition, which can effectively reduce the degradation cost. Therefore, we construct a photo-Fenton system by introducing Fe elements into MOF. Fe ions can provide abundant active sites to participate in the photo-Fenton catalytic system.
[0007] However, most single-phase photocatalytic materials have low light absorption capacity, high recombination rate of photogenerated electrons and holes, and poor catalyst stability, which limits the practical application of photocatalytic technology. Therefore, it is necessary to find suitable means to modify MOF to improve the photocatalytic activity. Summary of the invention
[0008] The purpose of the present invention is to provide an iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor and a preparation method and application thereof.
[0009] To achieve the above object, the present invention provides the following technical solutions:
[0010] One of the technical solutions of the present invention is to provide a method for preparing an iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor, comprising the following steps:
[0011] The iron-based metal organic framework material is added to a solution containing soluble molybdate and thiourea, mixed evenly and then subjected to hydrothermal reaction to obtain the iron-based metal organic framework @MoS2; the iron-based metal organic framework @MoS2, an alcohol solution containing an alcohol-soluble cadmium salt and a sodium sulfide solution are mixed, and the reaction is stirred to obtain the iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor.
[0012] Preferably, the ratio of molybdenum to thiourea in the iron-based metal organic framework material and the soluble molybdate is 0.1 g: (1-2) mmol: (2-4) mmol.
[0013] Preferably, the temperature of the hydrothermal reaction is 80-160° C., and the time is 24-36 hours.
[0014] Preferably, the ratio of cadmium to sodium sulfide in the iron-based metal organic framework @MoS2 and the alcohol-soluble cadmium salt is 0.1g:(0.2~0.4)mmol:(0.2~0.4)mmol.
[0015] Preferably, the iron-based metal organic framework material is NH2-MIL-88B (Fe); the soluble molybdate is sodium molybdate; and the alcohol-soluble cadmium salt is cadmium nitrate.
[0016] More preferably, the preparation step of NH2-MIL-88B(Fe) comprises: mixing a surfactant, an iron salt, acetic acid and 2-aminoterephthalic acid in water, and obtaining NH2-MIL-88B(Fe) after a hydrothermal reaction.
[0017] Further preferably, in the preparation of NH2-MIL-88B(Fe), the surfactant may be Pluronic F127, and the dosage ratio of the surfactant, acetic acid, iron element in the iron salt and 2-aminoterephthalic acid is 0.32 g:0.6 mL:1.32 mol:0.66 mol; the temperature of the hydrothermal reaction is 110°C, and the time is 24 h.
[0018] The second technical solution of the present invention: provides an iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor prepared according to the preparation method of the above-mentioned iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor.
[0019] The third technical solution of the present invention is to provide an application of the above-mentioned iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor in Fenton oxidation photocatalyst.
[0020] Technical solution four of the present invention: provides an application of the above-mentioned iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor in catalytic oxidation of organic pollutants.
[0021] The present invention introduces oxygen vacancies into molybdenum sulfide (MoS2) having the characteristics of narrow band gap, good chemical stability, large specific surface area, and resistance to light corrosion through defect engineering. Oxygen-defective MoS2 has a low band gap and can effectively enhance its light capture ability. Since the special lattice and adjustable band structure of MoS2 can be well matched with certain semiconductors, MoS2 is often combined with other photocatalysts to prepare high-performance photocatalysts. Studies have found that CdS and MoS2 can be well matched to form heterojunction composite catalysts, accelerate the separation of photogenerated carriers, and improve photocatalytic performance. However, the valence band (VB) and conduction band (CB) edges of MoS2 are both located within the band gap of CdS, forming a cross-band arrangement, and photogenerated holes and electrons are transferred from CdS to MoS2, resulting in a high recombination rate of photogenerated carriers in MoS2. Therefore, a hole acceptor is needed as a bridge to control the transmission of holes in the CdS / MoS2 heterojunction. The iron-based MOF introduced in the present invention has a high specific surface area and abundant cluster coordination, and can serve as a suitable hole acceptor between CdS and MoS2.
[0022] Based on the above considerations and verification assumptions, an iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor was prepared by hydrothermal method and in-situ deposition method, and a photo-Fenton system for in-situ generation of hydrogen peroxide was constructed. On the one hand, through the rational design of the band structure, the hierarchical core-shell structure with double Z-type heterojunction was shown to exhibit efficient sunlight capture ability and photocatalytic performance. On the other hand, the introduction of defects into MoS2 further expanded the light absorption range, thereby reducing the band gap.
[0023] The beneficial technical effects of the present invention are as follows:
[0024] The present invention prepares a novel iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor by a simple hydrothermal and in-situ deposition method, and successfully constructs a photo-Fenton system for in-situ generation of H2O2 under visible light. Compared with other pure samples, the nanoreactor shows better performance than photo-Fenton, with the removal rates of OFL and MO reaching 98.4% and 99.5% within 180 minutes. The improvement in efficiency may be attributed to the following reasons: (1) The designed defect engineering in MoS2 provides sufficient ligand vacancies to generate more active sites, while the large specific surface area of the layered MoS2 nanosheets contains a large number of edge active sites, which is conducive to charge carrier separation and photo-Fenton reaction. (2) The constructed core-shell double Z-type heterostructure nanoreactor makes NM88B act as a bridge between MoS2 and CdS, which is beneficial to shorten the electron-hole pair transmission distance and prolong the carrier lifetime. (3) The introduction of MoS2 and CdS not only improves the performance of NM88B in photo-Fenton generation of H2O2, but also promotes the Fe 2+ / Fe 3+cycle, thus significantly improving the photo-Fenton degradation performance.
[0025] The present invention provides ideas for constructing an efficient MOF heterojunction photo-Fenton system and also offers new insights into solving environmental problems. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Flow chart of preparing NM88B@MoS2 / CdS in Example 1.
[0027] Figure 2 XRD pattern a and FT-IR spectrum b of NM88B, NM88B@MoS2, NM88B@MoS2 / CdS prepared in Example 1, MoS2 prepared in Comparative Example 1, and CdS prepared in Comparative Example 2.
[0028] Figure 3 Scanning electron microscope images, transmission electron microscope images and elemental mapping images of NM88B, NM88B@MoS2, NM88B@MoS2 / CdS prepared in Example 1 and MoS2 prepared in Comparative Example 1, wherein a and b are scanning electron microscope images of NM88B, c is a scanning electron microscope image of MoS2, d is a transmission electron microscope image of NM88B, e is a transmission electron microscope image of, f is a high-resolution transmission electron microscope image of, and g is an elemental mapping image of NM88B@MoS2 / CdS.
[0029] Figure 4 This is the XPS analysis spectrum of NM88B@MoS2 / CdS prepared in Example 1, wherein a is the full spectrum, b is Fe2p, c is Mo 3d, d is Cd 3d, e is S2p, f is O1s, g is C1s, and h is N1s.
[0030] Figure 5 UV-visible spectra a, band gap energy curve b, EIS graph c and photocurrent intensity graph d of NM88B, NM88B@MoS2 and NM88B@MoS2 / CdS prepared in Example 1.
[0031] Figure 6 These are the results of ultraviolet diffuse reflection of NM88B, NM88B@MoS2 and NM88B@MoS2 / CdS prepared in Example 1.
[0032] Figure 7a) Steady-state photoluminescence spectra of NM88B, NM88B / MoS2 and NM88B@MoS2 / CdS, b) photo-Fenton degradation performance of OFL by NM88B@MoS2 / CdS at different pH values, c) photo-Fenton degradation efficiency and d) of OFL by NM88B, NM88B / MoS2, NM88B@MoS2 / CdS, MoS2 and CdS at pH = 5, e) stability cycle test of photocatalytic degradation of OFL by NM88B@MoS2 / CdS, and f) the amount of hydrogen peroxide produced by NM88B, NM88B / MoS2, NM88B@MoS2 / CdS, MoS2 and CdS during Fenton oxidation.
[0033] Figure 8 Figure 2 shows the photo-Fenton degradation efficiency a and first-order reaction rate curve b of MO by NM88B, NM88B / MoS2, NM88B@MoS2 / CdS, MoS2 and CdS at pH = 5.
[0034] Fig. 9 XRD patterns of NM88B@MoS2 / CdS before and after 5 cycles.
[0035] Fig.10 Scanning Kelvin probe images of NM88B, NM88B / MoS2, and NM88B@MoS2 / CdS. a. DMPO-·OH and DMPO-·O2 in the presence of NM88B@MoS2 / CdS - ESR signal and schematic diagram of the possible mechanism of NM88B@MoS2 / CdS photocatalytic Fenton reaction.
[0036] Fig.11 The degradation rate of OFL and MO under different conditions of NM88B@MoS2 / CdS.
[0037] Fig.12 Mott-Schottky curves of NM88B (a), MoS2 (b) and CdS (c).
[0038] Fig.13 are the band gap values of MoS2 (a) and CdS (b).
[0039] Fig.14 This is the charge transfer mechanism of NM88B@MoS2 / CdS. DETAILED DESCRIPTION
[0040] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0041] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0044] Example 1
[0045] Preparation of iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor:
[0046] (1) 0.32 g of Pluronic F127 (surfactant) was dissolved in 26.7 mL of deionized water, 3.3 mL of 0.4 M FeCl3·6H2O (1.32 mmol) was added, and 0.6 mL of acetic acid was injected after stirring for 1.5 h. After further stirring for 1.5 h, 120 mg of 2-aminoterephthalic acid (0.66 mmol) was added and stirred for 2 h. Then, the obtained mixture system was transferred to an autoclave and hydroheated at 110° C. for 24 h. The dark brown solid product was recovered and washed with ethanol by centrifugation for 5 times to remove the surfactant and excess reactants. Finally, it was dried at 60° C. for 8 h to obtain a reddish brown powder NH3-MIL-88B (Fe), denoted as NM88B.
[0047] (2) 0.31 g Na2MoO4·2H2O (1.3 mmol) and 0.29 g thiourea (3.8 mmol) were dissolved in 40 mL ultrapure water and stirred for 2 h to form a uniform solution; then, 0.1 g NM88B prepared in step (1) was added while stirring, and then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and heated at 110°C for 36 h; after natural cooling, the product was centrifuged and washed with deionized water and ethanol; finally, the product was dried in an oven at 60°C for 12 h, and the obtained sample was recorded as NM88B@MoS2;
[0048] (3) Take 0.1 g of NM88B@MoS2 and add it to 100 mL of 0.002 M Cd(NO3)2 ethanol solution, stir for 1 h, and ultrasonicate for 2 h. Then, add 100 mL of 0.002 M Na2S solution and continue stirring and reacting for 4 h. The product is centrifuged and collected to obtain an iron-based metal organic framework@MoS2 / CdS double Z-type heterojunction nanoreactor, recorded as NM88B@MoS2 / CdS.
[0049] Example 1 Flow chart of preparing NM88B@MoS2 / CdS Figure 1 .
[0050] Comparative Example 1
[0051] Preparation of MoS2:
[0052] 0.31 g Na2MoO4·2H2O (1.3 mmol) and 0.29 g thiourea (3.8 mmol) were dissolved in 40 mL ultrapure water and stirred for 2 h to form a uniform solution; then transferred to a polytetrafluoroethylene-lined stainless steel autoclave and heated at 110 °C for 36 h; after natural cooling, the product was centrifuged and washed with deionized water and ethanol; finally, the product was dried in an oven at 60 °C for 12 h to obtain MoS2.
[0053] Comparative Example 2
[0054] Preparation of CdS:
[0055] 100 mL of 0.002 M Cd(NO3)2 ethanol solution was mixed with 100 mL of 0.002 M Na2S solution, stirred for reaction for 4 h, and the product was separated and collected by centrifugation to obtain CdS.
[0056] The XRD patterns a and FT-IR spectra b of NM88B, NM88B@MoS2, NM88B@MoS2 / CdS prepared in Example 1, MoS2 prepared in Comparative Example 1, and CdS prepared in Comparative Example 2 are shown in Figure 2 .
[0057] Figure 2 It shows that NM88B has an obvious infrared peak at 3410cm -1 and 3490cm -1 The characteristic peaks observed at 1382 cm-1 and 1372 cm-2 are attributed to the symmetric and asymmetric stretching vibrations of the NH bond, respectively. -1 and 1583cm -1 The peak at 1268 cm -1 The peak at 774 cm corresponds to the stretching motion of the carbon-nitrogen bond. -1The characteristic absorption at 1127cm is related to the stretching vibration of the Fe-O bond, which is due to the formation of a metal-oxygen bond between Fe(III) and the organic ligand. -1 and 1610cm -1 The peaks belonging to the Mo-S bond were found at 627, 1020, 1110, 1382 and 1630 cm-1. The characteristic diffraction peaks of MoS2 can be observed in the infrared spectra of NM88B@MoS2 and NM88B@MoS2 / CdS, indicating that MoS2 was successfully loaded on NM88B. -1 There are several characteristic peaks at the NM88B@MoS2 / CdS composite material, but due to the low CdS content, some characteristic peaks are not obvious.
[0058] The scanning electron microscope images, transmission electron microscope images and elemental mapping images of NM88B, NM88B@MoS2, NM88B@MoS2 / CdS prepared in Example 1 and MoS2 prepared in Comparative Example 1 are shown in Figure 3 , where a and b are scanning electron microscope images of NM88B, c is a scanning electron microscope image of MoS2, d is a transmission electron microscope image of NM88B, e is a transmission electron microscope image of, f is a high-resolution transmission electron microscope image of, and g is an elemental mapping image of NM88B@MoS2 / CdS.
[0059] from Figure 3 A and Figure 3 In b, it can be observed that the diameter of NM88B is about 50nm and the length is 150-200nm. High-resolution transmission electron microscopy shows that the arrangement of the pores inside NM88B is disordered ( Figure 3 (c). Figure 3 Figure d is a transmission electron microscope image of MoS2, which shows that MoS2 is in the form of two-dimensional nanosheets. The transmission electron microscope image of the ternary composite material NM88B@MoS2 / CdS shows that a layer of folded nanosheets is formed on the surface of NM88B, and irregular CdS quantum dots are irregularly dispersed in the MoS2 nanosheets ( Figure 3 e). The high-resolution transmission electron microscope image clearly shows the lattice fringes of CdS and MoS2, where the lattice spacing of 0.67nm belongs to the MoS2 (002) crystal plane and the lattice spacing of 0.336nm belongs to the CdS (111) crystal plane. However, MOF is easily destroyed by the electron beam during the test, and the lattice fringes are difficult to distinguish after partial magnification ( Figure 3 f). From the element mapping diagram ( Figure 3 As can be seen in g), Fe, S, Mo and Cd elements are uniformly dispersed in the sample, further proving the formation of NM88B@MoS2 / CdS heterojunction photocatalyst. The above morphological observations are consistent with the results of XRD and FT-IR, confirming the successful synthesis of the ternary composite material.
[0060] In order to confirm the chemical state and surface element composition of the prepared samples and to better understand the interaction between NM88B, MoS2 and CdS QDs, X-ray photoelectron spectroscopy (XPS) analysis was performed on the NM88B@MoS2 / CdS prepared in Example 1. The analysis results are shown in Figure 4 , where a is the full spectrum, b is Fe 2p, c is Mo 3d, d is Cd 3d, e is S2p, f is O1s, g is C1s, and h is N1s.
[0061] from Figure 4 As can be seen in Figure a, the full spectrum of NM88B@MoS2 / CdS can prove that the main elements Fe, Mo, Cd, S, O, C and N of the composite sample coexist. Figure 4 As can be seen in b, the emission spectrum of Fe 2p is divided into four peaks, of which 717.7 eV is Fe 3+ The satellite peaks of Fe 3+ is the main form of Fe in the composite, with the main peaks at 710.7 and 724.0 eV, corresponding to Fe 2p 3 / 2 and Fe2p 1 / 2 Orbital, Fe 2p 1 / 2 Deconvolution of the peaks showed two peaks at 724.0 eV and 728.7 eV, corresponding to Fe 2+ and Fe 3+ chemical environment. Figure 4 In c, the two peaks at 231.7 and 228.6 eV show that Mo 4+ 3d 3 / 2 and Mo 4+ 3d 5 / 2 The presence of Mo in the composite material 6+ and Mo 5+ The characteristic peaks of further confirmed the oxygen doping in defective MoS2, which is consistent with the XRD analysis; in addition, Figure 3 A peak centered at 225.8 eV belonging to S2s can also be observed in the c of Cd 3d. The Cd 3d spectrum shows two peaks at 411.2 eV and 405.5 eV, which are respectively related to the Cd 3d 3 / 2 and Cd 3d 5 / 2 Related( Figure 4 (d) Figure 4 The characteristic peaks of S2s in e are centered at 162.7eV and 161.5eV, corresponding to S2p 1 / 2 and S2p 3 / 2 , confirming the presence of S in the nanocomposite. Figure 4In f, the peaks at 530.4, 529.6 and 529.0 eV are characteristic signals of water, hydroxyl and lattice oxygen adsorbed in the nanocomposite, respectively. Figure 4 g) shows three peaks at 284.7, 285.8 and 288.4 eV. Taking C as the sample, the characteristic peak at 288.4 eV is related to the carboxylic acid group (OC=O), the peak at 285.8 eV represents the organically connected CN, and the peak at 284.7 eV is C=C / CC. In the N spectrum ( Figure 4 In h), the XPS peak at 397.8 eV corresponds to the CN bond, and the XPS peak at 399.0 eV corresponds to the NH bond in the amino group.
[0062] The present invention evaluates the optical properties of NM88B, NM88B@MoS2 and NM88B@MoS2 / CdS by UV-visible diffuse reflectance (DRS) spectroscopy. In order to reveal the effect of light absorption performance on the activity of photocatalysts, the band gap energy (Eg) of the above catalysts was estimated by the Kubelka-Munk method. The lifetime of the photoinduced carrier is a key factor in the visible light photocatalytic reaction. Generally speaking, a longer carrier lifetime can improve the photocatalytic performance. The separation and transfer ability of the photogenerated electron-hole pairs of the above catalysts was further measured by electrochemical impedance spectroscopy (EIS) and transient photocurrent experiments.
[0063] The UV-visible spectra of NM88B, NM88B@MoS2 and NM88B@MoS2 / CdS prepared in Example 1 are shown in Fig. Figure 5 .
[0064] from Figure 5 It can be clearly observed in a that NM88B has a broad absorption peak at 200-800nm, indicating that it has strong absorption capacity for ultraviolet and visible light. Compared with NM88B, the light response ability of NM88B@MoS2 is enhanced, indicating that the introduction of defective MoS2 can significantly improve the light response range of NM88B, expanding the light response range from the ultraviolet and visible regions to the infrared region. This means that the composite material has potential photothermal effect. The composite material NM88B@MoS2 / CdS maintains a wider range of light absorption. This is because the close contact between MOF, MoS2 and CdS forms a heterojunction structure, thereby improving the light response ability. In addition, the results of ultraviolet diffuse reflection of NM88B, NM88B@MoS2 and NM88B@MoS2 / CdS prepared in Example 1 are shown in Figure 6 ,like Figure 6 As shown, the color of the photocatalyst corresponds to the result of diffuse UV reflection.
[0065] Figure 5Figure b shows that the Eg values of NM88B, NM88B / MoS2 and NM88B@MoS2 / CdS are approximately 1.97, 1.85 and 1.62 eV, respectively. The DNM88B@MoS2 / CdS composite photocatalyst has a narrower band gap, and the reduction of the band gap can effectively improve the utilization of light and the dissociation of photogenerated electron-hole pairs, thus broadening the visible light response range of NM88B, which in turn helps to improve the photocatalytic performance.
[0066] exist Figure 5 In the c, the electrochemical impedance spectroscopy (EIS) spectrum shows that NM88B@MoS2 / CdS has the smallest radius, representing the smallest impedance, which indirectly confirms that the resistance of charge transfer in the material is small, which is conducive to the transfer of photoinduced carriers. The transient photocurrent response of the prepared sample is shown in Figure 5 As shown in (d), it is clear that NM88B@MoS2 / CdS has the highest photocurrent response among all samples, which indicates that the ternary composite structure has the highest photoinduced electron transfer efficiency. This is due to the reasonable structural design of the ternary composite material, which causes the transport and separation of photoinduced carriers, which is crucial for the effective separation of photoelectron-hole pairs and the realization of efficient photocatalysis. The above results show that the introduction of cadmium sulfide quantum dots and defective MoS2 promotes charge separation and can further improve the photocatalytic performance of the photocatalyst.
[0067] The migration and separation efficiency of photogenerated electron-hole pairs have a great influence on the photocatalytic activity, so steady-state photoluminescence (PL) test was used to detect the mobility and separation efficiency of photogenerated electron-hole pairs in the material. The degradation performance of each sample on the organic compound ofloxacin (OFL) was further tested.
[0068] Steady-state photoluminescence spectra of NM88B, NM88B / MoS2 and NM88B@MoS2 / CdS a, Photo-Fenton degradation performance of OFL by NM88B@MoS2 / CdS at different pH values b, Photo-Fenton degradation efficiency of OFL by NM88B, NM88B / MoS2, NM88B@MoS2 / CdS, MoS2 and CdS at pH = 5 c and first-order reaction rate curves d, Stability cycle test of photocatalytic degradation of OFL by NM88B@MoS2 / CdS e (condition: [catalyst] = 0.4 g L -1 , [OFL] = 10 mg L -1 , time = 180 min), the amount of hydrogen peroxide produced by NM88B, NM88B / MoS2, NM88B@MoS2 / CdS, MoS2 and CdS during Fenton oxidation (condition: [catalyst] = 1 g L -1 , time = 180min) Figure 7 .
[0069] Figure 7 Figure a shows that among the three tested materials, NM88B@MoS2 / CdS has the lowest PL emission intensity, indicating the lowest recombination of photoinduced carriers. This is due to the recombination of MoS2 nanosheets and CdS quantum dots, indicating that the formation of heterojunction can hinder the recombination of photogenerated electron-hole pairs and prolong the carrier lifetime.
[0070] Figure 7 Figure b shows that within the pH range of 5-11, the ternary complex exhibits the best OFL degradation performance at pH = 5 when all other conditions remain unchanged. The oxidation efficiency of pollutants in an alkaline environment is greatly reduced compared to that in an acidic environment, which is attributed to the formation of iron hydroxide complexes on the surface of the photocatalyst when the pH is too high, resulting in a reduced ability to oxidize pollutants.
[0071] Therefore, the present invention selects pH=5 to evaluate the degradation of different photocatalysts. Figure 7 Figure c shows that within the 30-min range of the dark reaction, OFL is difficult to be eliminated. Then the photocatalytic degradation efficiency is measured every 30 min. Compared with pure NM88B, defective MoS2 and CdS, the degradation rate of the ternary composite has a significant advantage. The degradation efficiency of the NM88B@MoS2 / CdS photocatalyst for the pollutant OFL can reach 98.4%. The first-order reaction rate curve ( Figure 7 Figure d) shows that the NM88B@MoS2 / CdS photocatalyst has the highest degradation rate when removing pollutants. The degradation curve is linear. The kinetic constant (k) of the reaction was calculated based on the slope. Among them, the degradation rate constant of NM88B@MoS2 / CdS is the highest. When organic pollutants are converted into methyl orange (MO), the photo-Fenton degradation efficiency a and the first-order reaction rate curve b of NM88B, NM88B / MoS2, NM88B@MoS2 / CdS, MoS2 and CdS for MO at pH = 5 are shown in Figure 8 , Figure 8 The same trend was observed, where more than 99% of methyl orange was degraded within 90 min under visible light irradiation, with an apparent reaction rate of 5.4 × 10 -2 min -1 , higher than single material and binary material.
[0072] Figure 7 Figure e shows that after 5 cycles, the photocatalytic degradation rate of NM88B@MoS2 / CdS decreased slightly, indicating that the composite photocatalyst has good stability and repeatability. The XRD patterns of NM88B@MoS2 / CdS before and after 5 cycles are shown in Figure 5. Fig. 9 , Fig. 9It shows that there is no obvious change in the crystal phase of the material before and after the reaction, so the composite material has good recyclability.
[0073] Figure 7 Figure f shows the amount of hydrogen peroxide produced by NM88B, NM88B / MoS2, NM88B@MoS2 / CdS, MoS2 and CdS during Fenton oxidation. Compared with the amount of hydrogen peroxide produced by NM88B, MoS2, CdS and the binary composite alone, the ternary composite can produce the most hydrogen peroxide. This may be due to the narrowing of the band gap by the design of the ternary composite heterojunction, which improves the charge separation efficiency and the activity of photocatalytic hydrogen peroxide generation, promoting the photo-Fenton reaction and generating oxygen free radicals.
[0074] Fig.10 Figure a is the scanning Kelvin probe (SKP) image of NM88B, NM88B / MoS2, and NM88B@MoS2 / CdS. DMPO-·OH and DMPO-·O2 in the presence of NM88B@MoS2 / CdS - ESR signal and schematic diagram of the possible mechanism of NM88B@MoS2 / CdS photocatalytic Fenton reaction.
[0075] Fig.10 Figure a shows that the work function of the NM88B@MoS2 / CdS photocatalyst is about 4.02 eV, which is the lowest value among NM88B, NM88B@MoS2 and NM88B@MoS2 / CdS, indicating that the electrons of this carefully designed material are more easily excited for photocatalytic reactions. Based on this result, a feasible mechanism for the NM88B / @MoS2 / CdS photocatalyst can be assumed. In order to explore the active radical components of the composite photocatalyst for pollutant degradation, free radical capture experiments were performed on the samples. Fig.11 ,like Fig.11 As shown in the figure, disodium ethylenediaminetetraacetate (EDTA-2Na), benzoquinone (BQ) and isopropyl alcohol (IPA) were used to capture holes (h + ), hydroxyl radicals (·OH) and superoxide radicals (·O2 - ). After adding EDTA-2Na, the degradation efficiency of DNM88B@MoS2 / CdS for OFL and MO was 83.7% and 86.2%, respectively, and the photocatalytic reaction was less restricted. However, when BQ and IPA were added, the photocatalytic degradation efficiency of the two pollutants was significantly reduced and obviously inhibited, proving that ·OH and ·O 2- It is the main active group in the photocatalytic degradation process and plays a key role in the reaction. In this system, the order of active groups in the catalytic degradation process is ·OH>·O 2- >h + .
[0076] Fig.10 Figure b shows that 5,5-dimethyl-1-pyrrolidine N-oxide (DMPO) was selected as a scavenger for obtaining free radicals. No DMPO-·O2 was recorded in NM88B@MoS2 / CdS in the dark. - There was no DMPO-·OH signal, indicating that no photocatalytic reaction occurred in the absence of light. However, after 3 minutes of visible light irradiation, the free radical signal responded significantly, which undoubtedly showed that both free radicals came from the photocatalytic process. DMPO-·OH had an obvious response and the signal could be clearly observed, confirming that ·OH was formed by the photo-Fenton reaction. At the same time, obvious DMPO-·O was also detected after illumination. 2- The response signal indicates that O2 is produced during the reaction. - The above test results are consistent with the results of free radical capture experiments, thus confirming the active groups ·OH and ·O 2- Played a major role in the system.
[0077] To further explore the mechanism of the photo-Fenton reaction of NM88B@MoS2 / CdS, the band gap (Eg), valence band (VB) and conduction band (CB) of NM88B, MoS2 and CdS were measured, and the results are shown in Table 1. In addition, the Mott-Schottky curves of NM88B (a), MoS2 (b) and CdS (c) are shown in Fig.12 .
[0078] Table 1
[0079]
[0080]
[0081] Fig.12 The tangent lines of all samples show positive slopes, indicating that NM88B, MoS2 and CdS are all n-type semiconductor photocatalysts. The conduction bands of NM88B, MoS2 and CdS are -0.16, -0.45 and -0.65 eV, respectively. The band gap values of the above catalysts were estimated using the Kubelka-Munk method, see Fig.13 The Eg values of NM88B, MoS2 and CdS are approximately 1.97, 1.87 and 2.4 eV, respectively. Therefore, the VB value of the semiconductor material can be determined by the following formula. The VB values (VB = CB + Eg) of NM88B, MoS2 and CdS are calculated to be 1.81, 1.42 and 1.75 eV, respectively.
[0082] The conduction band (CB) and valence band (VB) positions of NM88B are both located below those of MoS2 and CdS, so two possible charge transfer pathways are proposed, including the traditional type II and double Z schemes. - was transferred to the CB of NM88B, thereby accumulating a large amount of e on the CB of NM88B - However, the CB value of NM88B (-0.16 eV) did not reach that of O2 / ·O 2- (-0.33eV) potential, and O2 cannot be e - Restore to O 2- , which is inconsistent with the experimental results of free radical capture and ESR. Therefore, the charge transfer pathway of NM88B@MoS2 / CdS follows a double Z scheme rather than a type II scheme. The mechanism diagram is shown in Fig.14 .
[0083] like Fig.14 As shown in Figure 2, NM88B acts as a linker to form a close contact heterojunction structure between MoS2 and CdS. The photoexcited electrons are transferred from the CB position of NM88B to the VB of MoS2 and CdS, and then interact with the h + Combination. h in NM88B VB with strong oxidative ability + and e in MoS2 and CdS CBs with strong reducing ability - Maintaining spatial separation inhibits the rapid recombination of carriers, thereby improving the activity of the photocatalytic Fenton reaction. The CB positions of MoS2 (-0.45 eV) and CdS (-0.65 eV) are more negative than O2 / ·O2 (-0.33 eV), which means that ·O2 radicals can be generated through oxygen reduction and directly participate in the degradation process of pollutants. Therefore, in the end, the photogenerated electrons gather in the CB of MoS2 and CdS and react with O2 to form ·O 2- Free radicals participate in pollutant removal. In addition, the VB of NM88B (1.81 eV) has not yet reached the OH- / ·OH potential (1.99 eV), and theoretically ·OH cannot be generated. However, according to the free radical capture experiment, the generation of ·OH may be obvious because the CB of O2 / H2O2 (0.69 eV) is more positive than the CB of NM88B (-0.16 eV). H2O2 can be obtained by O2 reduction and participate in the photo-Fenton reaction.
[0084] Photogenerated carriers promote the Fe 3+ Reduction to Fe 2+ , through Fe 3+ Reacts with H2O2 to produce Fe 2+ and OOH, Fe 2 +Can maintain reaction with H2O2 and produce Fe 3+ and ·OH, which promotes Fe 2+ / Fe 3+ The unsaturated iron clusters provide abundant Fe-CUS, thus enhancing the Fe 2+ / Fe 3+ In addition, the photogenerated electrons on CB are beneficial to the redox ability of ·OH and ·O in the Fenton process to a certain extent. 2- The generation of active groups effectively increases the number of active groups, further enhancing the photocatalytic activity.
[62] The heterojunction superstructure can effectively promote carrier separation, inhibit electron-hole pair recombination, and expand the light response range, thereby significantly improving the photocatalytic Fenton activity.
[0085] The photo-Fenton reaction process is as follows:
[0086] NM88B@MoS2 / CdS+hv→e - +h + (1)
[0087] O2+e - → O2 - (2)
[0088] O2 - +2H + →H2O2 (3)
[0089] Fe 2+ +H2O2→Fe 3+ + OH+OH - (4)
[0090] Fe 3+ +H2O2=Fe 2+ +·OOH+H + (5)
[0091] OH / O2 - / h + +pollutants→H2O+CO2 (6)
[0092] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing an iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor, characterized in that: The following steps are involved: The iron-based metal organic framework material is added to a solution containing soluble molybdate and thiourea, mixed evenly and then subjected to hydrothermal reaction to obtain the iron-based metal organic framework @MoS2; the iron-based metal organic framework @MoS2, an alcohol solution containing an alcohol-soluble cadmium salt and a sodium sulfide solution are mixed, and the reaction is stirred to obtain the iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor.
2. The method for preparing the iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor according to claim 1, characterized in that: The usage ratio of molybdenum to thiourea in the iron-based metal organic framework material and the soluble molybdate is 0.1 g: (1-2) mmol: (2-4) mmol.
3. The method for preparing the iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 80-160° C. and the time is 24-36 hours.
4. The method for preparing the iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor according to claim 1, characterized in that: The usage ratio of cadmium to sodium sulfide in the iron-based metal organic framework @MoS2 and the alcohol-soluble cadmium salt is 0.1g:(0.2-0.4)mmol:(0.2-0.4)mmol.
5. The method for preparing the iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor according to claim 1, characterized in that: The iron-based metal organic framework material is NH2-MIL-88B (Fe); the soluble molybdate is sodium molybdate; and the alcohol-soluble cadmium salt is cadmium nitrate.
6. The method for preparing the iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor according to claim 5, characterized in that: The preparation steps of the NH2-MIL-88B(Fe) include: mixing a surfactant, acetic acid, an iron salt and 2-aminoterephthalic acid in water, and then performing a hydrothermal reaction to obtain NH2-MIL-88B(Fe).
7. An iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor prepared according to the preparation method of the iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor according to any one of claims 1 to 6.
8. Application of the iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor described in claim 7 in Fenton oxidation photocatalyst.
9. Application of the iron-based metal organic framework @MoS2 / CdS double Z-type heterojunction nanoreactor described in claim 7 in catalytic oxidation of organic pollutants.
Citation Information
Patent Citations
Fe2O3-MoS2-CdS visible photocatalysis film, and preparation method and application thereof
CN107020140A
Sulfide-containing industrial wastewater treatment reagent and reaction method thereof
CN107720930A
CdS / metallic organic frame composite photocatalysis material as well as preparation method and application thereof
CN109331883A
Preparation method of sulfide heterojunction material capable of resisting photocorrosion in photo-Fenton reaction
CN109453792A
Composite catalyst of MoS2 / defective MIL-100 (Fe) and preparation method and application thereof
CN111659468A